A wide temperature insensitive piezoceramics for high‐temperature energy harvesting. Issue 9 (12th March 2019) - Zhao, Haiyan; Hou, Yudong; Yu, Xiaole; Fu, Jing; Zheng, Mupeng; Zhu, Mankang
Abstract: One of the key challenges in the development of high‐temperature energy harvesting (HTEH) technology is to clarify the relationship between temperature‐dependent material parameters and device power generation capabilities. However, at present, the research on temperature stability of piezoceramics mainly relies on thermal annealing technology, which cannot follow the actual temperature dependence of the piezoelectricity, and it is even more difficult to predict the temperature stability of HTEH. To shed light on this field, here, (1− x )BiScO3 – x PbTiO3 system was chosen for building HTEH material, and the temperature‐dependent electrical parameters, such as d 33, ε r, and g 33, have been measured by multiple in situ techniques. It was found that the synergistic effect of d 33 and ε r with temperature helps to obtain a stable g 33 value in a wide temperature range. Moreover, in the mode of the cantilever‐type energy harvester, a stable output voltage was obtained at x = 0.64 harvester with <20% change over a broad temperature range of 100‐250°C, and it was verified that the temperature stability of g 33 is crucial to the operation stability of HTEH devices.